2007
DOI: 10.2215/cjn.03931106
|View full text |Cite
|
Sign up to set email alerts
|

Screening, Diagnosis, and Treatment of Cancer in Long-Term Dialysis Patients

Abstract: Some have suggested that the American Cancer Society guidelines for cancer screening be applied to patients who are on long-term dialysis and have used cancer screening as a means of assessing delivered preventive health care to patients with ESRD. However, cancer screening is effective only when it leads to survival benefit (usually expressed as days of life saved) without incurring high financial costs. Certain cancers such as human papillomavirus-associated cervical and tongue cancer and urologic malignanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 50 publications
2
81
0
3
Order By: Relevance
“…Previous studies have shown an increased overall risk of cancer in persons with ESRD requiring RRT, [4][5][6][7][8][9][10][11] but the impact of less severe kidney dysfunction and cancer risk has been less certain. [12][13][14][15] In contrast to our findings, two prior studies found an association between renal function and overall cancer risk, 13,14 whereas another study found no association between CKD and cancer risk in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown an increased overall risk of cancer in persons with ESRD requiring RRT, [4][5][6][7][8][9][10][11] but the impact of less severe kidney dysfunction and cancer risk has been less certain. [12][13][14][15] In contrast to our findings, two prior studies found an association between renal function and overall cancer risk, 13,14 whereas another study found no association between CKD and cancer risk in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although multiple studies have observed higher risks of cancer in persons with ESRD requiring dialysis or renal transplantation, [4][5][6][7][8][9][10][11] whether less severe kidney disease is associated with cancer remains poorly understood. [12][13][14][15] Previous studies are limited by modest sample sizes, restricted diversity, and their ability to adequately control for confounders.…”
mentioning
confidence: 99%
“…Thus, because the CKD-ESRD population has a higher prevalence of cancer and the CKD-ESRD population is increasing, more precise dosing recommendations for this population are needed. 31 One suggestion would be for the regulatory agencies, such as the U.S. Food and Drug Administration and the European Medicines Agency, to encourage that essential data on renal and dialysis clearance on new chemotherapeutic agents be made available. Monitoring renal function in patients receiving chemotherapy is essential; however, using serum creatinine in malnourished patients with cancer can overestimate kidney function, thereby risking chemotoxicity.…”
Section: Unique Features Of Nephrologic Disorders In Cancermentioning
confidence: 99%
“…Previous studies have shown that patients suffering from ESRD belong to such populations. The increased risk of cancer applies to both patients on dialysis and recipients of renal grafts (2)(3)(4)(5). In recipients of organ transplants, the occurrence of malignancies has been strongly linked to the use of immunosuppressive agents, because such agents impair the body's ability to locate and destroy cancer cells and control viral infections related to cancer (6).…”
Section: Introductionmentioning
confidence: 99%